Integrative Analysis of Sex-Specific microRNA Networks Following Stress in Mouse Nucleus Accumbens - Pfau, Madeline L.; Purushothaman, Immanuel; Feng, Jian; Golden, Sam A.; Aleyasin, Hossein; Lorsch, Zachary S.; Cates, Hannah M.; Flanigan, Meghan E.; Menard, Caroline; Heshmati, Mitra; Wang, Zichen; Ma'ayan, Avi; et al. (Frontiers in Molecular Neuroscience, 2016)
Adult women are twice as likely as men to suffer from affective and anxiety disorders, although the mechanisms underlying heightened female stress susceptibility are incompletely understood. Recent findings in mouse Nucleus Accumbens (NAc) suggest a role for DNA methylation-driven sex differences in genome-wide transcriptional profiles. However, the role of another epigenetic process—microRNA (miR) regulation—has yet to be explored. We exposed male and female mice to Subchronic Variable Stress (SCVS), a stress paradigm that produces depression-like behavior in female, but not male, mice, and performed next generation mRNA and miR sequencing on NAc tissue. We applied a combination of differential expression, miR-mRNA network and functional enrichment analyses to characterize the transcriptional and post-transcriptional landscape of sex differences in NAc stress response. We find that male and female mice exhibit largely non-overlapping miR and mRNA profiles following SCVS. The two sexes also show enrichment of different molecular pathways and functions. Collectively, our results suggest that males and females mount fundamentally different transcriptional and post-transcriptional responses to SCVS and engage sex-specific molecular processes following stress. These findings have implications for the pathophysiology and treatment of stress-related disorders in women.